2017
DOI: 10.1186/s12906-017-1842-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pomegranate extracts on brain antioxidant markers and cholinesterase activity in high fat-high fructose diet induced obesity in rat model

Abstract: BackgroundTo investigate beneficial effects of Pomegranate seeds oil (PSO), leaves (PL), juice (PJ) and (PP) on brain cholinesterase activity, brain oxidative stress and lipid profile in high-fat-high fructose diet (HFD) induced-obese rat.MethodsIn vitro and in vivo cholinesterase activity, brain oxidative status, body and brain weight and plasma lipid profile were measured in control rats, HFD-fed rats and HFD-fed rats treated by PSO, PL, PJ and PP.ResultsIn vitro study showed that PSO, PL, PP, PJ inhibited c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 59 publications
7
30
0
Order By: Relevance
“…The reduced litter size also decreased GPx activity in the hypothalamus. In agreement, 12 weeks of high-fat diet decreased GPx activity in adult rat brain (Amri et al, 2017), showing a negative effect of overnutrition. SOD and GLO1 activities were improved on EO pups, demonstrating a positive response, which may be caused by an adapting effect of exercise over the pro-inflammatory environment caused by litter reduction (Ziko et al, 2014).…”
Section: Discussionsupporting
confidence: 74%
“…The reduced litter size also decreased GPx activity in the hypothalamus. In agreement, 12 weeks of high-fat diet decreased GPx activity in adult rat brain (Amri et al, 2017), showing a negative effect of overnutrition. SOD and GLO1 activities were improved on EO pups, demonstrating a positive response, which may be caused by an adapting effect of exercise over the pro-inflammatory environment caused by litter reduction (Ziko et al, 2014).…”
Section: Discussionsupporting
confidence: 74%
“…Among them are resveratrol and quercetin that may possess thermogenic properties [91], oleuropein able to enhance catecholamine secretion [92] or kaempferol increasing thyroid hormone activation [93] having influence on the slimming process. Similar effects were obtained with Hibiscus sabdariffa [70], pomegranate [94] or oolong tea [95,96] extracts rich in polyphenols. Molecular and cellular investigations demonstrated that these herbal-derived polyphenols reduce the viability of adipocytes and proliferation of preadipocytes, inhibit adipocyte differentiation and triglyceride accumulation, stimulate lipolysis and fatty acid β-oxidation, and reduce inflammation.…”
Section: Secondary Plant Metabolitessupporting
confidence: 67%
“…In our experiment, the activity of antioxidant enzymes increased in response to combined treatment (ROT+PJ) with the exception of SOD activity (data not shown herein). Accumulating evidence supports the inducing effect of pomegranate [7,52,53] and its active compound punicalagin [43,54] on the endogenous antioxidant system in different experimental models. We demonstrated a trend toward enhancing the endogenous antioxidant system following treatment with pomegranate juice alone; the increase was significant only for GPx activity.…”
Section: Discussionmentioning
confidence: 85%